Studies on the reproductive effects of chronic treatment with agomelatine in the rat - Canpolat, Sinan; Ülker, Nazife; Yardımcı, Ahmet; Bulmuş, Özgür; Özdemir, Gökçen; Şahin, Zafer; Ercan, Zübeyde; Serhatlıoğlu, İhsan; Kaçar, Emine; Özcan, Mete; Türk, Gaffari; Özkan, Yusuf; et al. (My University, 2016)
Agomelatine is an antidepressant with a novel mechanism of action. It is a melatonergic agonist for MT1 and MT2 receptors and a serotonin (5-HT2C) receptor antagonist. Agomelatine has been suggested not to have adverse effects on sexual functions. However, the effects of chronic agomelatine administration on reproductive functions have not been sufficiently studied in animal models. We mainly aimed to explore the effects of agomelatine on reproductive functions in the male and female rats. For the experimental studies, Sprague Dawley rats were used. The animals started to receive daily oral agomelatine (10mg/kg) on post-natal day 21. Agomelatine advanced vaginal opening in the female rats whereas it delayed puberty onset in the male rats. Agomelatine treatment significantly decreased intromission frequencies, which indicates a facilitator role of this antidepressant on male sexual behavior. In the forced swimming test (FST) used for assessing antidepressant efficacy, agomelatine induced a significant decrease in duration of immobility, and an increase in the swimming time, respectively, which confirms the antidepressant-like activity of agomelatine. The present findings suggest that agomelatine shows a strong antidepressant effect in the male rats without any adverse influences on sexual behavior, and its effects on pubertal maturation seem to show sex-dependent differences.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Agomelatine; Antidepressant; Sexual behavior